2015
DOI: 10.1186/s12889-016-2692-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise changes on body composition during the college years - a five year randomized controlled study

Abstract: BackgroundObservational studies have consistently reported severe weight gains during the college years; information about the effect on body composition is scarce, however. Thus, the aim of the study was to determine the effect of exercise changes on body composition during 5 years at university.MethodsSixty-one randomly selected male and female dental (DES; 21 ± 3 years., 22 ± 2 kg/m2) and 53 sport (physical education) students (SPS; 20 ± 2 years., 22 ± 3 kg/m2) were accompanied over their 5-year study progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
(42 reference statements)
3
10
2
3
Order By: Relevance
“…statistically significant differences in this area occur not earlier than after two years of intensive sport training [14]. However, the research shown here confirms regularities observed by Kemmler et al [17]. The researchers have proved that undertaking vigorous physical activity is essential for the body mass index of tested individuals.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…statistically significant differences in this area occur not earlier than after two years of intensive sport training [14]. However, the research shown here confirms regularities observed by Kemmler et al [17]. The researchers have proved that undertaking vigorous physical activity is essential for the body mass index of tested individuals.…”
Section: Discussionsupporting
confidence: 79%
“…In many studies, there were relevant dependences observed between sports activity and physical fitness [15,16]. A very important research topic seems to be the time for sports activity, which, according to many researchers, determines changes of the morphological characteristics and physical fitness [17]. sport and physical activity is an important and compulsory part for the people who connect their lives with the military system.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Colby et al (2017) detected an inverse relationship between BMI and physical activity. The differences in results seen in the study by Kemmler et. al (2016) may be due to the two groups of students studied.…”
Section: Physical Activity In College Studentscontrasting
confidence: 58%
“…Analogous to the previous study by Strohacker et al (2015), all participants in this research study by Gu et al (2015) were female, and thus a similar study should be conducted with both male and female participants before these results can be generalized to the entire college student population. Kemmler, von Stengel, Kohl, & Bauer (2016) determined that physical activity did not decrease during college, but exercise (which was defined within the research study as individual or group sports) did decline in both students studying dentistry as well as students studying physical education when compared to other majors. However, this same research study also noted that dental students gained twice as much fat as lean body mass, whereas physical education students gained solely lean body mass during this same timeframe.…”
Section: Physical Activity In College Studentsmentioning
confidence: 95%
See 1 more Smart Citation